Study of Community Based Ecotourism Development in Mangrove Area of Mempawah District, West Kalimantan - Hurriyani, Yeni (AQUASAINS, 2019)
Mangrove forests as natural ecosystems, have high ecological and economic value. Rapidly growing population, causing the needs of human life is increasing, as a consequence of increased development and settlement. This will create pressure on natural resources, where the utilization has not yet taken into consideration any losses that have ecological impacts. Implementation of ecotourism system in mangrove forest ecosystem is an approach in sustainable utilization of mangrove forest ecosystem. The ecosystem suitability index for mangrove tourism in Village Pasir Mempawah Hilir Mempawah District is classified into very suitable (SS) and conditional (SB) categories for ecotourism development. This shows that the mangrove area in the Village Pasir Mempawah Hilir Mempawah District is suitable to serve as a tourist area. An alternative strategy of ecotourism management of mangrove priority in the coastal area of Pasir Village, Mempawah Hilir, Mempawah District, is to increase the effort of mangrove planting on the beach (replanting) in ecotourism development area. Thus, all areas in the location meet the criteria appropriate for mangrove ecotourism areas based on ecological parameters.